The effect of congenital toxoplasmosis on some Biochemical levels of serum and blood contents of pregnant women infected in Mosul - Gasan Alobaydi (College of Education for Pure Sciences, 1970)
ABSTRACT The study included (45) samples of blood from pregnant women, which are positive to Toxoplasma gondii by latex agglutination test, and (10) sample of blood from pregnant women, which are negative to Toxoplasma gondii. All pregnant women in two groups are in the first three months of pregnancy and the age of both groups was the same. Results show a significant decrease (p≤0.05) in glucose level and also in hemoglobin, platelets and red blood cells count with an increase in white blood cells count when compared with control group. Glutamate Pyruvate Transaminase (GPT), Glutamate Oxaloacetate Transaminase (GOT) enzymes in serum of pregnant women, infected with toxoplasmosis, show a significant increase (p≤ 0.05) when compared with control group. On the other hand, Alkaline Phosphatase (ALP) show a significant increase (p≤ 0.05) when compared with control group.